2022
DOI: 10.1177/00034894221100024
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Otolaryngology’s NIH Research Funding Compared to Other Specialties

Abstract: Objective: To compare NIH funding in the field of Otolaryngology to other medical and surgical specialties between 2009 and 2019. Methods: Data was collected from the NIH RePORTER database on funding dollars received by each specialty from 2009 to 2019. Along with data on total active physicians per specialty using the Physician Specialty Data Book, comparisons were drawn between Otolaryngology and other medical and surgical specialties with regards to trends in total funding and NIH funding dollars per physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…However, K grants are better represented among surgeon-scientists than PIs with a PhD degree since many K grants are tailored to clinician-scientists and therefore are not available to individuals with a PhD degree . In a comparison of NIH funding per physician across surgical specialties, OHNS was first in 2010; third following neurosurgery and ophthalmology in 2013, 2015, and 2017; and fourth behind neurosurgery, ophthalmology, and general surgery in 2019 . When R and U grant amounts per physician were delineated, we also found that otolaryngologists received less funding than neurosurgeons.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…However, K grants are better represented among surgeon-scientists than PIs with a PhD degree since many K grants are tailored to clinician-scientists and therefore are not available to individuals with a PhD degree . In a comparison of NIH funding per physician across surgical specialties, OHNS was first in 2010; third following neurosurgery and ophthalmology in 2013, 2015, and 2017; and fourth behind neurosurgery, ophthalmology, and general surgery in 2019 . When R and U grant amounts per physician were delineated, we also found that otolaryngologists received less funding than neurosurgeons.…”
Section: Discussionmentioning
confidence: 72%
“…10 In a comparison of NIH funding per physician across surgical specialties, OHNS was first in 2010; third following neurosurgery and ophthalmology in 2013, 2015, and 2017; and fourth behind neurosurgery, ophthalmology, and general surgery in 2019. 5 When R and U grant amounts per physician were delineated, we also found that otolaryngologists received less funding than neurosurgeons. However, the data showed that OHNS had more R and U grant funding per physician than ophthalmology in 2016, 2017, 2019, and 2021, a contrast from the conclusion by Ramsey et al 5 and may be associated with differences between R and U grant funding and all NIH grant funding.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations